Prevention of Liver Cancer Through the Early Detection of Risk-Related Behavior Among Hepatitis B or C Carriers. Issue 3 (May 2015) - Fan, Jun-Yu; Huang, Tung-Jung; Jane, Sui-Whi; Chen, Mei-Yen
Abstract : Background: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are the leading causes of liver cirrhosis and hepatocellular carcinoma. Little is known about the relationship between health-related behaviors and health status among HBV or HCV carriers. Objective: The purpose of this study was to explore the relationship between health status (eg, specific biomarkers) and health-related behaviors (eg, alcohol consumption) in individuals with or without HBV or HCV infection. Methods: A cross-sectional descriptive design was used, and a community-based health screening survey was conducted between August 2011 and July 2012 in Taiwan. Results: In total, 6 805 community residents 20 years or older participated in the study. The HBV and HCV infection rate was 18.7% and 20.8%, respectively, and HBV/HCV infections were significantly associated with current alcohol use, smoking, and self-medication. Multivariate analysis indicated that HBV/HCV infection, overweight status, higher fasting blood sugar level, higher systolic blood pressure, and 3 unhealthy habits were independent risk factors for abnormal liver function. Conclusion: Our findings suggest that both HBV and HCV carriers are more likely to have unhealthy habits and a poor health status. In addition to some factors that cannot be modified, being overweight, drinking alcohol, betel nut chewing, smoking, and self-medication are all risk factors for poor liver health among both hepatitis carriers. Implications for Practice: For clinicians, the results could be applied by providing more education to help the community better understand the relationships between specific risk factors and liver health, encouraging hepatitis carriers in rural areas to undergo annual physical check-ups.